Developing and managing organizational learning : a guide to effective training project management - OVERFIELD, KAREN (AMERICAN SOCIETY FOR TRAINING & DEVELOPMENT ALEXANDRIAUS, 1998)
Provides a step-by-step guide for developing and managing corporate training programmes. Explains tasks including: how to conduct a present/future analysis; construct a programme design; construct an instructional design; cost a project; implement and evaluate a programme. Lists the resources needed for each step, and uses diagrams, tables, case studies, and sample forms to illustrate and support the concepts.